Perbandingan Tindakan Euthanasia Aktif dan Pasif Dalam Tinjauan Hukum Positif Indonesia - Taufik, Ficqhi; Hidjaz, Muh. Kamal; Aswari, Aan (Program Pascarajana Universitas Muslim Indonesia, 2023)
The aim of this research is to determine active euthanasia and forms of criminal responsibility. And to know the act of passive euthanasia and its forms of accountability. The results of this research show that Active Euthanasia requires a doctor to take direct action, either by giving a high dose injection, or by removing a medical device that can help or provide care to the patient. The act of Active Euthanasia has not been explicitly regulated in Indonesian legal regulations, but the article that is closest to it, if you look at the elements of the act of active euthanasia, is the article that is closest to Active Euthanasia in Article 344 of the Criminal Code. And in contrast to active euthanasia, cases of passive euthanasia often surface or are often encountered. Passive euthanasia often receives an explanation where the doctor does not provide any more treatment or action to a patient who should receive treatment. Of course, passive euthanasia is also not clearly regulated in Indonesian law, but if you look at the elements of passive euthanasia, the closest thing is Article 304 of the Criminal Code.